Under-Dam Water Level Indicator and Warning System Via SMS and WhatsApp - SOULISOMBOON, Dee; SOUKHAVONG, Sengthong; SIPHAXAY, Khamphoungeun; KEOPASEUTH, Pathoumphone; NAMPANYA, Bouthsady (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research aimed to design and test the under-dam water level indicator and warning system via SMS and WhatsApp. The system was designed by applying JSN-SR04T Ultrasonic Sensor and ESP8266 NodeMCU microcontroller, consuming power supply from solar power with 4 levels of notification. If the water level reaches the pre-set threshold value, the ESP8266 NodeMCU Microcontroller triggers the alarm by notification to LCD display, lamp, speaker, and phone with a short message (SMS) and WhatsApp as well as storing water level data in Google Sheets to be able to check the value of water level data. According to the research results, the developed system can work and notify the water level accordingly to the purpose, can send notification messages to mobile phones according to the designed notification level. The developed system can store and check the water level data in Google Sheets. From the actual experiments, the developed system has working efficiency up to 98.38%.